Frequency, Type and Cause of Artifacts in Swept-Source and Cirrus HD Optical Coherence Tomography in Cases of Glaucoma and Suspected Glaucoma. (2nd July 2016) - Lee, Sang Yeop; Kwon, Hee Jung; Bae, Hyoung Won; Seo, Sang Jin; Lee, Yun Ha; Hong, Samin; Seong, Gong Je; Kim, Chan Yun
ABSTRACT: Purpose : To evaluate and compare the frequency, type and cause of imaging artifacts incurred when using swept-source optical coherence tomography (SS OCT) and Cirrus HD OCT in the same patients on the same day. Materials and methods : From left eye OCT results of 72 patients, disc area and macular area data could be compared between the two types of OCT. For each scan, the final printout report and source data were examined. For comparison between the two types of OCT, only source image data were used because of differences in the final printout report format. Results : There were no significant differences in the artifact frequencies between the two groups in either area (disc area: 35.9% of SS OCT, 42.2% of Cirrus OCT, p = 0.523; Macular area: 24.2% of SS OCT, 22.7% of Cirrus OCT, p = 1.00). The overall results of artifact comparison between the two types of OCTs also showed no significant differences. Boundary misidentification was the most common type of artifact observed, and ocular pathology was the most common cause of artifact in both types of OCTs. Among ocular pathologies, the epiretinal membrane (ERM) was the most common cause of OCT artifact production in both types of OCTs. Conclusions : There was no significant difference in the frequency, type and cause of artifacts between SS OCT and Cirrus HD OCT. Artifacts in OCT can influence the interpretation of OCT results. In particular, ERM around the optic disc could contribute to OCT artifacts and should be considered in glaucoma diagnosis or during patient follow-up using OCT.